(untitled) (International Journal of Environmental Sciences, 2025)
This study aimed to evaluate the impact of a micro-learning based flipped classroom model on the academic performance and engagement of first-year biology university students. The experimental group was exposed to the micro-learning based flipped classroom model, while the control group followed traditional teaching methodologies. The research was structured into four distinct phases. The initial phase involved collecting baseline data to ascertain both students’ and teachers’ perspectives on the current educational practices. The second phase was dedicated to the development of the flipped classroom model. The third phase of the study focused on the experimental deployment of the model, examining its effectiveness. The data revealed that the experimental group significantly outperformed the control group in terms of academic performance. Furthermore, enhanced engagement levels were observed among the experimental group.The final phase of the study confirmed a strong preference among students for the micro-learning based flipped classroom model over traditional teaching approaches. These findings advocate for the integration of flipped classroom and micro-learning strategies to augment the learning experiences and outcomes in biology education.